GREEN FINANCE DISCLOSURE BERBASIS MAQASHID SYARIAH DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS - Raodahtul (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2025)
This study aims to analyze how green finance disclosure is applied by Bank Muamalat KCP Gowa with reference to maqashid syariah principles. This study focuses on the relationship between these disclosure practices and the achievement of the Sustainable Development Goals (SDGs). This research is included in the type of qualitative research with a phenomenological approach. The research location is at Bank Muamalat KCP Gowa, Gowa Regency, South Sulawesi. The data used in this study consisted of primary data and secondary data. Primary data was obtained through in-depth interviews with internal bank parties and customers, while secondary data was obtained from journals, websites and annual reports of Bank Muamalat. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results showed that Bank Muamalat KCP Gowa has implemented the principles of green finance through service digitization programs, energy efficiency, and financing that pay attention to sustainable aspects. The implementation of maqashid sharia-based green finance disclosure at Bank Muamalat KCP Gowa regarding implementation in supporting its existence consists of five maqashid sharia principles such as preserving religion (hifdz al-din), preserving the soul (hifdz al-nafs), preserving the mind (hifdz al-'aql), preserving offspring (hifdz al-nasl) has been implemented, while preserving property (hifdz al-mal) requires financing for the agricultural sector. The implementation of green finance disclosure based on maqashid sharia in realizing SDGs is seen from the achievement of social, economic and environmental aspects. This success is reflected in the contribution of Bank Muamalat in supporting SDGs in line with the five main pillars in maqashid sharia.